Widgets : The 12 New Rules for Managing Your Employees as if They're Real People - Wagner, Rodd (McGraw-Hill's AccessEngineering., 2015)
"New York Times bestselling author Rodd Wagner tackles one of the most destructive problems facing organizations today-the breakdown of the relationship between employees and the organizations they work for. "Your people are not your greatest asset. They're not yours, and they're not assets.". With this declaration, one of the leading authorities on employee performance rolls up his sleeves against the weasel words, contradictions, bad habits, and intrusions that reduce people to "human resources." To "FTEs." To "human capital." To flesh-and-blood widgets. Armed with empirical evidence from the provocative studies he leads around the globe, Wagner guides you through the new realities of what it takes to get the highest levels of intensity from people in a more mercenary, skeptical, and wired work world. He explains how elements such as individualization, fearlessness, transparency, recognition, and coolness are reciprocated with loyalty, productivity, innovation, and--inescapably--corporate reputation .".